Evaluation of retinal vascular calibers in overweight an obese Malay children - Siang, Chai Khai (2017)
Background: There are limited studies on retinal vascular caliber in overweight and obese children especially for Malays who is the main ethnicity in South East Asia. Purpose: The present study aims to determine the mean and mean differences of retinal arteriolar caliber and retinal venular caliber between overweight and obese among Malay children. Methods: This was a cross-sectional study involved 131 Malay children aged 6-12 years in Kota Bharu, Malaysia. Overweight and obese groups were identified based on sex and age specific World Health Organization 5 to 19 years old growth chart. Multi-stage random sampling method was employed in participants’ recruitment. Ocular examination, refraction, retinal photograph and anthropometric measurement including height, weight and blood pressure were obtained by standardized protocols. Retinal vascular caliber was measured using a validated computer-based program Singapore I Vessel Algorithm software and were summarized as the retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) by using the Kudtson-Parr-Hubbard formula. Ocular magnification on retinal vascular vascular caliber measurement was corrected by using the Bengtsson formula. Analysis of Covariance was performed to determine mean differencebetween overweight and obese Malay children after adjusted with significant confounding factors. Results: The mean corrected CRAE in overweight and obese Malay children were 173.50 μm and 165.84 μm respectively whereas the mean corrected CRVE in overweight and obese Malay children were 252.37 μm and 253.41 μm respectively. There was a significant mean difference of retinal arteriolar caliber between overweight and obese Malay children where narrower retinal arteriolar caliber was observed in obese than overweight. However, there was no significant mean difference of retinal venular caliber between overweight and obese Malay children after adjustment for confounding variable. Conclusions: Retinal arteriolar caliber was found narrower in obese than the overweight Malay children. However, The mean retinal venular caliber was almost similar in both groups. This may suggest that pediatric obesity has an effect on the microvasculature early in childhood. This study triggers the awareness of preventing children as early as overweight period in order to halt the potential undesired systemic diseases later on in obesity period.